Targeted and Osteo-Oncologic Treatment in Early Breast Cancer: What Is State-of-the-Art and What Might Become so within the Next 5 Years? - Stickeler, Elmar (S. Karger GmbH, 2014)
In 2014, modern strategies of targeted therapies in the adjuvant setting are mainly focused on anti-human epidermal growth factor receptor 2 (HER2) blockade. For the 15% of HER2-enriched tumors, 1 year of treatment with the monoclonal antibody trastuzumab is the standard of care. All patients, regardless of tumor size, nodal status, or age, profit from therapy with risk reduction rates for recurrence of up to 50%. As a consequence, the current guidelines recommend the use of trastuzumab in these patients if additional risk factors lead to the consideration of adjuvant chemotherapy. The concurrent use with taxane-based chemotherapy is preferred. The concept of dual HER2 blockade – already approved in the metastatic setting – shows also significantly improved efficacy in neoadjuvant trials. Dual blockade with trastuzumab and pertuzumab is approved by the Food and Drug Administration (FDA) for neoadjuvant treatment of HER2-overexpressing tumors. However, until approved in Europe, this treatment approach remains off-label for early breast cancer and study participation is highly recommended. Bisphosphonates (BPs) and denosumab are approved in breast cancer as standard therapy for the treatment of bone metastases. In the adjuvant setting, BPs and denosumab can be given to prevent tumor therapy-induced bone loss. The antineoplastic effect of BPs in the adjuvant setting and its role in the prevention of metastatic disease are still under discussion.